Lipid-Based Drug Carriers for Prodrugs to Enhance Drug Delivery - Zaro, Jennica L. (AAPS J, 2014)
The combination of lipid drug delivery systems with prodrugs offers several advantages including improved pharmacokinetics, increased absorption, and facilitated targeting. Lipidization and use of lipid carriers can increase the pharmacological half-life of the drug, thus improving pharmacokinetics and allowing less frequent dosing. Lipids also offer advantages such as increased absorption through the intestines for oral drug absorption and to the CNS for brain delivery. Furthermore, the use of lipid delivery systems can enhance drug targeting. Endogenous proteins bind lipids in the blood and carry them to the liver to enable targeting of this organ. Drugs with significant side effects in the stomach can be specifically delivered to enterocytes by exploiting lipases for prodrug activation. Finally, lipids can be used to target the lymphatic system, thus bypassing the liver and avoiding first-pass metabolism. Lymphatic targeting is also important for antiviral drugs in the protection of B and T lymphocytes. In this review, both lipid-drug conjugates and lipid-based carriers will be discussed. An overview, including the chemistry and assembly of the systems, as well as examples from the clinic and in development, will be provided.